Patterns of Behavior of State Civil Apparatus in The Implementation of E-Government (Case Study in The Regional Secretariat of Bantul District, Indonesia) - Denny Ardiansyah Pribadi; Suswanta Suswanta (Journal of Governance and Public Policy, 2024)
The main subject of this research is the behavior patterns of civil servants in dealing with changes in e-government. This study aims to determine the behavior patterns of Civil Servants at the Regional Secretariat of Bantul Regency. The theory used is the bureaucratic theory by Miftha Thoha, formulated in five aspects, namely Capability, Needs, Trust, Experience, and Expectations, and implementation theory by Edward III, which is developed in four aspects: communication, resources, dispositions, and bureaucratic structure. This study uses a qualitative method. The informants were leaders at the Regional Secretariat of Bantul Regency who were taken using a purposive sampling technique. Data collection techniques consisted of observation, interviews, and documentation, while data analysis techniques involved data reduction, data presentation, and conclusion drawing (verification). The results showed that the civil servants' behavior patterns in implementing e-government at the Regional Secretariat of Bantul Regency have not been carried out optimally, as seen from the design of behavior and e-government. Aspects of trust have not gone well either. Trust has not been earned because it is hindered by employees' ability at 50 years and over. Regarding e-government, aspects of resources and bureaucratic structure still have obstacles. There are also several deficiencies. Parts of the bureaucratic system have obstacles to differences in employee benefits between heads of subdivisions and current functional positions. Therefore, leaders need to make a work plan to meet these needs. Ways that need to be taken to deal with this problem include encouraging employees aged 50 years and over and providing them with technology training, adding employees through broad selection, and understanding employees who have experienced reduced employee benefits.